DETEKSI DINI VIRUS MOSAIK PADA BENIH DAN TANAMAN NILAM / Detection of Early Stage of Mosaic Disease on Patchouli Seed and Plant - Rita Noveriza; Maya Mariana (Jurnal Penelitian Tanaman Industri, 2016)
Mosaic disease of patchouli plant caused by viruses is one of the main constraints on patchouli oil production. The viruses are transmitted by patchouli seedlings and insect vectors, therefore their spreadings are very quickly and widely found in the center of patchouli plantations in Sumatera, Java, and Sulawesi. Early detection of the viruses in the seedling is a strategic step for controlling the disease. This study aimed to get an early detection technique of mosaic viruses infecting seedlings and patchouli plants by using serological techniques. This research was conducted at the Laboratory of Plant Protection Balittro from February 2015 until April 2016. The serological techniques performed were Tissue Blot Assay Immunobinding (TBIA), Dot Immuno Binding Assay (DIBA) and Enzyme Linked Immuno Assay (ELISA). Samples of the seedlings and patchouli plants showing symptomatic mosaic disease were obtained from nurseries or fields in Bogor, Pandeglang-Banten and Cigombong. A total of 150 samples were tested using the commercial viruses antisera, i.e. Potyvirus, Broad bean wilt virus 1.2; Cucumber mosaic virus [AGDIA-USA] and Anti-Mouse, Rabbit Anti Universal [SIGMA-USA]. The results showed that all the three serological tests used can detect all types of mosaic viruses in infected seedling and patchouli plants with a success rate of 100%. The TBIA and DIBA techniques are faster and easier than ELISA, therefore these techniques are recommended to be used by farmers and patchouli seed producers to prevent the distribution of mosaic viruses.Keywords: P ogostemon cablin, mosaic virus, ELISA, TBIA, DIBA AbstrakPenyakit mosaik yang disebabka n oleh virus merupakan salah satu kendala utama pada produksi minyak nilam. Virus tersebut ditularkan melalui benih nilam dan serangga vektor sehingga penyebarannya sangat cepat dan sudah banyak ditemukan di sentra pertanaman nilam di Sumatera, Jawa dan Sulawesi. Deteksi dini virus pada benih nilam merupakan langkah strategis untuk mengendalikan penyakit. Penelitian ini bertujuan untuk mendapatkan teknik deteksi dini virus penyebab penyakit mosaik pada benih dan tanaman nilam secara serologi, sehingga mudah diaplikasikan oleh petani dan pengguna di lapangan. Penelitian ini dilakukan di Laboratorium Proteksi Tanaman Balittro dari bulan Februari 2015 sampai dengan bulan April 2016. Teknik deteksi secara serologi yang dilakukan adalah Tissue Blot Immunobinding Assay (TBIA), Dot Immuno Binding Assay (DIBA) dan Enzyme Linked Immuno Assay (ELISA). Sampel benih dan tanaman nilam bergejala mosaik diperoleh dari pertanaman atau penangkar benih di Bogor, Pandeglang-Banten dan Cigombong-Kabupaten Bogor. Sebanyak 180 sampel diuji keberadaan virusnya dengan menggunakan antisera komersial, yaitu Potyvirus, Broad bean wilt virus 1.2; Cucumber mosaic virus (AGDIA-USA) dan Anti Mouse, Anti Rabbit Universal (SIGMA-USA). Hasil yang diperoleh menunjukkan bahwa ketiga teknik serologi yang diuji dapat mendeteksi seluruh jenis virus yang menimbulkan gejala mosaik pada benih dan tanaman nilam, dengan tingkat keberhasilan 100%. Teknik deteksi TBIA dan DIBA mosaik lebih cepat dan mudah dibandingkan dengan ELISA sehingga dapat dianjurkan kepada petani dan penangkar benih nilam untuk mencegah penyebaran virus mosaik, karena lebih cepat dan mudah digunakan.Kata kunci: Pogostemon cablin, virus mosaik, ELISA, TBIA, DIBA